Soluble Factors on Stage to Direct Mesenchymal Stem Cells Fate - Sobacchi, Cristina; Palagano, Eleonora; Villa, Anna; Menale, Ciro (Frontiers in Bioengineering and Biotechnology, 2017)
Mesenchymal stem cells (MSCs) are multipotent stromal cells that are identified by in vitro plastic adherence, colony-forming capacity, expression of a panel of surface molecules, and ability to differentiate at least toward osteogenic, adipogenic, and chondrogenic lineages. They also produce trophic factors with immunomodulatory, proangiogenic, and antiapoptotic functions influencing the behavior of neighboring cells. On the other hand, a reciprocal regulation takes place; in fact, MSCs can be isolated from several tissues, and depending on the original microenvironment and the range of stimuli received from there, they can display differences in their essential characteristics. Here, we focus mainly on the bone tissue and how soluble factors, such as growth factors, cytokines, and hormones, present in this microenvironment can orchestrate bone marrow-derived MSCs fate. We also briefly describe the alteration of MSCs behavior in pathological settings such as hematological cancer, bone metastasis, and bone marrow failure syndromes. Overall, the possibility to modulate MSCs plasticity makes them an attractive tool for diverse applications of tissue regeneration in cell therapy. Therefore, the comprehensive understanding of the microenvironment characteristics and components better suited to obtain a specific MSCs response can be extremely useful for clinical use.